Increasing Critical Thinking Abilities and Skills through Problem Based Learning for Elementary School Students - Ardiansya, Vendra Oktareno; Minsih, Minsih; Negara, Santosa Pradana Putra Setya; Mujiono, Nanang Sri (Buletin KKN Pendidikan, 2024)
The study aimed to evaluate the effectiveness of problem-based learning in enhancing critical thinking skills in Natural and Social Sciences. It utilized a quasi-experimental design with pretest-posttest randomized control groups. Data analysis involved t-tests to determine group differences and N-gain to measure improvement. Results showed significant enhancement in critical thinking abilities with problem-based learning. The t-test indicated a significant difference between groups, with t count (5.949) exceeding the t table value (2.018) and p-value (0.000) below 0.05. N-Gain scores showed a higher improvement in the experimental group (48.65%) compared to the control (29.46%). These findings highlight the effectiveness of problem-based learning in fostering critical thinking.